The effect of ethnoscience-based course review horay learning towards cultural concept understanding and science process skills of the elementary school students - Mudana, Wayan (Nurture, 2023)
Purpose: This research aims to analyze the effect of the ethnoscience-based course review horay learning model on the understanding of cultural meaning understanding and science process skills of students at the elementary school level. Design/Methodology/Approach: This study is quasi-experimental in nature, with a nonequivalent post-test only control group design. The sample of this study comprised 29 students in the experimental group and 28 students in the control group, making a total sample size of 57 participants. Data was collected using a test method consisting of 10 essay items to measure cultural meaning understanding, and a questionnaire consisting of 30 statements to assess science process skills. Inferential statistical analysis and quantitative descriptive analysis were the two methods used for data analysis. Findings: The research findings showed that the ethnoscience-based course review horay learning model had a significant effect on both cultural meaning understanding and science process skills, both simultaneously and partially. This was demonstrated by a significant difference in mean values and sig value<0.05 for both cultural meaning understanding and science process skills between the experimental and control groups. Conclusion: The findings also suggested that science process skills were more strongly influenced by the ethnoscience-based course review horay model compared to the understanding of cultural meaning, which is indicated by the larger mean difference observed in the former. Therefore, it is recommended that the ethnoscience-based course review horay learning model be utilized as an innovative learning model to address the issue of low levels of both cultural meaning understanding and science process skills among elementary school students.